After eighty years of misidentification, a name for the glass catfish (Teleostei: Siluridae) - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2013)
We resolve the identity of the glass catfish, a species of Asian freshwater fish commonly encountered as an ornamental fish and an experimental subject that has long been misidentified as either Kryptopterus bicirrhis or K. minor. Our study indicates that the glass catfish is an unnamed species distinct from either, which we describe here as Kryptopterus vitreolus. Kryptopterus vitreolus is known from river drainages in peninsular and southeastern Thailand, and is distinguished from congeners in having a combination of: transparent body in life, maxillary barbels reaching beyond the base of the first anal-fin, dorsal profile with a pronounced nuchal concavity, snout length 29–35% head length (HL), eye diameter 28–34% HL, slender body (depth at anus 16–20% standard length (SL)) and caudal peduncle (depth 4–7% SL), 14–18 rakers on the first gill arch, and 48–55 anal-fin rays.